Nutritional Status and Gross Motor Skills: Study of children in coastal areas - Riska Ramadani Lasri; Tjung Hauw Sin; Wilda Welis; Sri Gusti Handayani; Septian Raibowo; Indri Wulandari; Yovhandra Ockta (Postgraduate, University of Mataram, 2024)
This study examines the relationship between nutritional status and gross motor development in children aged 1-3 years in coastal areas with limited economic and infrastructure conditions. The aim of the study was to evaluate the correlation between nutritional status and gross motor abilities. A cross-sectional design with correlation analysis was employed. Data were collected through anthropometric measurements of nutritional status and gross motor skills assessment using the Pre-Development Questionnaire (KPSP). Results indicated that 50% of children were malnourished, while 33.3% showed deviations in gross motor skills. The correlation between nutritional status and gross motor development had a coefficient of 0.75, indicating a strong relationship. The t-test revealed a significant association (t = 5.136; t-table = 1.701). The conclusion of this study is that poor nutritional status negatively impacts children's gross motor development, whereas good nutritional status supports optimal physical and motor development. Recommendations include enhancing attention to children's nutritional intake and providing appropriate stimulation, along with further research to explore additional factors influencing gross motor development.